(untitled) (Research, Society and Development, 2024)
It is delimited as cancer during pregnancy, those detected from the first weeks to 12 months of the puerperium, based on the physiological changes that occur during pregnancy, which are related to hormonal changes. The therapy, which has not yet been precisely defined for cases of gynecological cancer, generates uncertainty in the medical team and psychological damage to the patient, who experiences the duality between fear of the diagnosis and hesitation about motherhood. Therefore, investigating strategies to adequately conduct the treatment of these patients will ensure an improvement in the prognosis and maternal and fetal well-being. The objective of the present work is to list and evaluate the therapeutic alternatives that are indicated for women who suffer from cervical cancer during pregnancy in its various periods. This study is a systematic literature review, based on studies found on the Scientific Electronic Library Online (SciELO) and PubMed platforms. Articles up to 10 years old were part of the verification present in this study (2013-2023). The words will be used: pregnancy, cervical cancer, treatment and prognosis. It is expected to obtain as a result a classification of conducts, based on the best prognosis of the disease, development of the fetus and maintenance of the pregnancy in order to avoid maternal-fetal complications.